Professional Training in The South-East Region of Romania: Analysis And Implications in The Agricultural Sector - Beatrice-Simona MANOLACHE; Rodica (Aparaschivei) Bîrlă; Silvius STANCIU (Communications of International Proceedings, 2023)
The research focuses on vocational training in the South-East Region of Romania and its implications in the agricultural sector. The study proposes to evaluate the effectiveness and relevance of the professional training programs implemented in the SE Region of Romania in the period 2018-2022. In this sense, statistical information was analyzed regarding the number of licenses granted for professional training programs in the six counties of the region, respectively the number of qualifications in the agricultural field. The study carried out focused on the identification of relevant trends and models related to vocational training in the agricultural sector of the South-East Region. The analysis of the statistical data shows the level of involvement of the authorities and training centers in the development and implementation of vocational training programs, as well as the degree of success in obtaining the necessary qualifications in the agricultural sector. The results of the research highlighted both positive aspects, as well as challenges and opportunities identified in professional training activities in the region. The implications of these actions in the context of regional agricultural development are analyzed in the article, offering recommendations and suggestions for improving the efficiency and relevance of professional training programs in the agricultural field. Additionally, the study examines the impact of vocational training on the skills and competences of individuals in the agricultural sector, as well as on the demand and supply of employees in the field. The shortage of skilled labor in the agricultural field can negatively affect the efficiency, productivity and innovation of companies. It is important to develop appropriate strategies and policies, including investing in training and education, promoting the attraction and retention of skilled workers, and facilitating access to technology and innovations in agriculture. The conclusions obtained from this analysis can contribute to the development of targeted policies and strategies, which encourage effective vocational training adapted to the region, support the sustainable development of the agricultural sector and increase the skills and quality of the agricultural workforce.
Keywords: professional training; human resources; qualification; agricultural field; Romania